Delivering bad news by physicians – Polish reality check - Sobczak, Krzysztof; Pawłowski, Leszek; Pietrzykowska, Małgorzata; Spolak, Natalia (Journal of Medical Science, 2016)
Introduction. Disclosing unfavorable information is a very important moment in both diagnostic and therapeutic processes. It is also a highly stress-inducing factor, both among patients and physicians. During our research we tried to establish how exactly bad news is communicated to patients and the amount of stress that Polish physicians are under in such situations.Material and Methods. Quantitative research was conducted in a university clinical hospital. With the use of an anonymous questionnaire, physicians (n = 100) from oncology, internal diseases, cardiac surgery, gynecology, obstetrics, and urology clinics were asked about the sources and the intensity of stress involved in BBN (Breaking Bad News). Similarly, patients (n = 378) of said clinics were asked to evaluate the relationships they had with their doctors. Results. Most (66.7%) clinicians declared they always conveyed unfavorable information to their patients fully and in detail. Exactly 50.0% admitted they were experiencing high or very high level of stress while doing so. They were mostly (56.1%) anxious about depriving their patients of hope and (38.5%) feared they were letting their patients down. 37.3% of clinicians were afraid of emotional response. Significantly fewer physicians (43%) than patients (84.6%) were of the opinion that all of the medical orders must be followed to the letter.Conclusions. Results suggest that BBN was a stressful experience for physicians. It was mostly related to the fear of disrupting the patient's well-being. Low level of effective communication was caused by the insufficiency of BBN skills. Social and cultural aspects also played a role.
Keywords: Clinical-Patient Communication; Doctor-Patient Relationship; Breaking Bad News